Odpowiedzi

2010-03-18T22:07:44+01:00
A) (3+2x)²=(3x+2)²+10
(3+2x)(3+2x)=(3x+2)(3x+2)+10
9+6x+6x+4x <kwadrat>=9x<kwadrat>+6x+6x+4+10
9+12x+4x<kwadrat>=9x<kwadrat>+12x+14 /-4x <kwadrat>
9+12x=5x<kwadrat>+12x+14 /-12x
9=5x <kwadrat>+14 /-14
-5=5x<kwadrat> /;5
-1=x <kwadrat> /<pierwiastkujemy>
pierwiastek z -1=x

e)(x-2)(x+2)=5
x<kwadrat>+2x-2x-4=5
x<kwadrat>-4=5 /+4
x<kwadrat>=9 / pierwiastkujemy
x=pierwiastek z 9
x=3
2 3 2
Najlepsza Odpowiedź!
2010-03-18T22:15:56+01:00
A) (3+2x)²=(3x+2)²+10
9+4x²+12x=9x²+4+12x+10
4x²+12x-9x²-12x=4+10-9
-5x²=5
-5x²-5=0
-5(x²+1)=0
x²+1=0
x²=-1

równanie sprzeczne, nie ma rozwiązania ponieważ nie ma pierwiastka drugiego stopnia z liczby ujemnej

b) (5x-2)(3-x)=-6(1-x)(1+x)
15x-5x²-6+2x=-6(1-x²)
17x-5x²-6=6x²-6
17x-11x²=0
-11x²+17x=0
-x(11x-17)=0

x=0 v x=17/11

c) x+9=(x-3)²
x+9=x²+9-6x
x+9-x²-9+6x=0
-x²+7x=0
-x(x-7)=0

x=0 v x=7

d) (4x-6)²=(x-4)(x-9)
16x²+36-48x=x²-9x-4x+36
16x²-48x-x²+9x+4x=0
15x²-35x=0
5x(3x-7)=0

x=0 v x=7/3=2⅓

e) (x-2)(x+2)=5
x²-4=5
x²=9
x²-9=0
(x-3)(x+3)=0

x=3 v x=-3
2 5 2